Pengaruh FDR, DPK, Promosi, Dan NPF Terhadap Pertumbuhan Aset Perbankan Syariah Di Indonesia (Studi Empiris Pada Bank Umum Syariah Yang Terdaftar Di OJK Periode 2013-2017) - Dea Cici Nofela; Safira Safira (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
This study aims to determine the effect of Finance Deposit Ratio (FDR), Third Party Funds (DPK)), Promotion Costs, and Non Performing Financing (NPF) on the Growth of Sharia Banking Assets in Indonesia. The population of this study issharia public banks registered at OJK during the period 2013-2017 with use annual financial report data.The research sample was selected using purposive sampling technique so that 11 Islamic banks were obtained meet the criteria. The analysis technique used is multiple regression using SPSS version 20.0 program. Based on the results of multiple regression analysis, the results of this study shows that FDR, DPK, Promotion, and NPF have a positive effect on the Growth of Sharia Banking Assets in Indonesia.